THE EFFECT OF THE FREQUENCY OF TIKTOK USE AND STUDENTS’ LIFESTYLE ON THEIR CONCENTRATION WHILE STUDYING - Elsa Sulistia Rini; Edris Zamroni; Nur Mahardika (Jurnal Kajian Pendidikan dan Psikologi, 2026)
This study aims to analyze the relationship between the intensity of TikTok use and students’ lifestyles and their concentration while studying in high school. The study employed a quantitative approach with a correlational design using multiple linear regression analysis. The study was conducted at SMAN 1 Mejobo, Kudus Regency, involving 290 students in grades 10, 11, and 12 who were selected using stratified random sampling. Data were collected using a four-point Likert scale questionnaire that measured the intensity of TikTok use, students’ lifestyles, and academic concentration. The instrument underwent validity and reliability testing, with an overall Cronbach’s alpha value of 0.844. Data analysis was performed using SPSS 23 through classical assumption tests, multiple linear regression, t-tests, F-tests, and the coefficient of determination. The results of the study indicate that the intensity of TikTok use is positively and significantly associated with academic concentration (β = 0.146; t = 4.207; p < 0.001). Students’ lifestyle also showed a positive and significant relationship with concentration while studying and had a more dominant predictive power (β = 0.773; t = 22.219; p < 0.001). Simultaneously, the two variables produced a significant model (F = 294.153; p < 0.001), with R = 0.820 and R² = 0.672. Thus, the model explains 67.2% of the variation in students’ concentration while studying. These findings underscore the importance of a comprehensive approach that integrates social media use management, self-regulation, time management, and the development of an academic lifestyle that supports concentration during study.